0448 Quantitative Evaluation of the Upper Airway during the Muller Maneuver in Controls and Apneics. (27th April 2018) - Brake, L A; Lin, T C; Keenan, B T; Azad, N; Nguyen, T T; Wiemken, A S; Goldberg, A N; Schwab, R J
Abstract: Introduction: Changes in airway caliber during periods of negative intraluminal pressure are fundamental in understanding the pathogenesis of obstructive sleep apnea (OSA). We evaluated the change in airway caliber in normal subjects and apneics during a normalized Muller maneuver (a forced inspiration). We hypothesized that apneics would exhibit greater airway collapse during negative intraluminal pressures compared to controls. Methods: Nasopharyngoscopy with the Muller maneuver was performed on 18 normal subjects (AHI<5; 0.7 ± 1.1 events/hour) and 30 apneics (AHI>15; 32.6 ± 28.5). Maximal effort maneuvers were performed in the supine and seated positions and changes in retropalatal (RP) and retroglossal (RG) regions quantified. Measures in the RP region were also quantified during graded pressures (-10, -20, -30, -40mmH2 O) while sitting. Results: Apneics were older (44.7 ± 12.1 vs. 30.2 ± 10.5 years, p=0.0001) and more obese (33.1 ± 7.6 vs. 25.2 ± 3.7 kg/m 2, p<0.0001) than controls; 80% of subjects were male. During maximal effort, controls showed reduced minimum cross-sectional area (CSA) in only the RP region in the supine (-63%, p<0.0001) and seated (-59%, p<0.0001) positions. 34–57% reductions were seen in the lateral dimension in both positions and regions (all p<0.0001). Apneics showed significantly reduced airway caliber during maximal pressures for all measures, regions and positions, except RG seated AP dimension. Reductions ranged from 22% in the RG supine AP dimension (p=0.0004) to 88% in seated RP minimal CSA (p<0.0001). Reductions in apneics were greater (all p<0.023) than those in controls for nearly all measures, regions and positions, except RG lateral and RP supine AP dimension. Seated graded efforts in the RP region showed reductions in all measures in both groups and greater reductions in apneics for pressures ≤ -20mmH2 O. Conclusion: Both groups showed significant reductions in RP airway caliber during maximal and graded efforts in both positions, while only apneics showed consistent reductions in the RG airway. Reductions in apneics were greater than those seen in controls, despite similar negative pressures. Examining a normalized Muller maneuver may provide important information about the site of airway narrowing in apneics. Support (If Any): Funded by NIH P01 HL094307.